SARS-CoV-2 Virion Stabilization by Zn Binding - Morante, Silvia; La Penna, Giovanni; Rossi, Giancarlo; Stellato, Francesco (Frontiers in Molecular Biosciences, 2020)
Zinc plays a crucial role in the process of virion maturation inside the host cell. The accessory Cys-rich proteins expressed in SARS-CoV-2 by genes ORF7a and ORF8 are likely involved in zinc binding and in interactions with cellular antigens activated by extensive disulfide bonds. In this report we provide a proof of concept for the feasibility of a structural study of orf7a and orf8 proteins. A conceivable hypothesis is that lack of cellular zinc, or substitution thereof, might lead to a significant slowing down of viral maturation.